Effect of NPK Fertilizers on Growth and Quality of Tomato (Solanum lycopersicum L.) Under Heavy Clay Soils of Patiala - Singh, Harsimranjeet; Kaur, Harpreet (International Journal of Economic Plants, 2022)
Study was conducted at Khalsa College Farm during the year 2019. The experiment was laid out in Randomized Block Design and replicated four times. The treatment comprised T1: control, T2: 50 % NPK, T3: 75 % NPK, T4: 100 % NPK, T5: 125 % NPK and T6: 150 % NPK. Among different treatments, T6: 150 % NPK was found to be superior for growth characters like plant height (73.56 cm), plant spread (93.36 cm), leaf length (7.02 cm) and number of branches plant-1 (17.60) which was followed by T5: 150 % NPK. Maximum quality characters like TSS (6.63°Brix) ascorbic acid (26.45 mg 100 g-1) and shelf life (12.85 days) were examined under T5: 125% NPK which was followed by T4: 100% NPK and T6: 150% NPK. It is clear from the present study that more doses of fertilizers play positive effect on growth and quality of tomato.